Análisis, diseño, construcción e implementación en ambiente de pruebas los módulos de Gestión de posiciones, Administración de personal y Reportería para manejo de información en el área de Talento Humano de la Superintendencia de Control del Poder de Mercado (SPCM) - Mena Carrasco, Nelly Tathiana (2016)
This paper addresses the development of a web application intended for process automation in the area of human talent of the Superintendencia de Control de Poder de Mercado (SCPM), specifically the construction of the modules: personnel administration and management positions. The application manages the following information: basic data of functionary, spouse data, disability, emergency contact, performs management of positions, assignment custom and / or subrogation, through the organization of processes for easy access to relevant information. Generates updated reports: personal information, historical positions, surrogacy and / or commissions. The document is structured in 3 detailed chapters: Chapter 1 presents the components of the project: background, system justification, objectives, theoretical framework with the concepts needed for construction, plus the information from the Superintendencia de Control de Poder de Mercado, its history and its organizational structure. Chapter 2 presents the analysis and system design using XP methodologies for monitoring the development of the application as it adapts to changing requirements and UWE for the preparation of technical documentation that will allow modeling web applications focused on the systematic design. Chapter 3 presents the used tools, the system development, the implementation of MVC software design and the testing to ensure proper system operation.